The new citizen armies : Israel's armed forces in comparative perspective - Cohen, Stuart, 1946- (London ; New York : Routledge, 2010)
This edited book constitutes the first detailed attempt at a comparative international analysis of the transformations that are currently affecting the composition of the Israel Defense Forces (IDF) and their place in Israeli society. Focusing primarily on deviations from the traditional norm of universal military service, the book compares the emergence of a new type of ""citizen army"" in Israel with the formats that have in recent decades become evident in other western democracies. In addition, these essays correct the conventional tendency to concentrate almost exclusivel.
Introduction / Stuart A. Cohen -- pt. 1. Continuities and their manifestations -- The enduring citizen-soldier tradition in the United States / Ronald R. Krebs -- Recruiting the all-volunteer force : continuity and change in the British Army, 1963-2008 / Christopher Dandeker -- The Royal Netherlands Army, 1814-2008 : the rise and decline of a citizen army? / Jan Hoffenaar -- Reversing the tide of Jewish history : culture and the creation of Israel's "people's army" / Stuart A. Cohen -- pt. 2. Change : causes and constraints -- Operational and technological incentives and disincentives for force transformation / Avi Kober -- Strategic and political factors preventing the shift from "citizen armies" to professional militaries / Gabriel Sheffer and Oren Barak -- Gender issues in the transformation to an all-volunteer force : a transnational perspective / Michelle Sandhoff, Mady Wechsler Segal, David R. Segal -- Conscription versus recruitment through markets : economic considerations / Yaacov Lifshitz -- The officer corps in the all-volunteer army : the American experiment continues / Leonard Wong -- Up from the ashes : the re-professionalization of the Canadian forces after the "Somalia" affair / David J. Bercuson -- pt. 3. Israeli dilemmas and experiences -- Where will the women be? : gendered implications of the decline of Israel's citizen army / Orna Sasson-Levy -- From the "citizen army" to the "market army" : Israel as a case study / Yagil Levy -- Teaching citizens to be professional soldiers : IDF responses and their implications / Tamir Libel.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Israel. -- Tseva haganah le-Yiśraʼel.; Israel. -- Tseva haganah le-Yiśraʼel; Israel -- Armed Forces; Civil-military relations -- Israel; Military art and science -- Cross-cultural studies; Relations pouvoir civil-pouvoir militaire -- Israël.; Art et science militaires -- Études transculturelles; HISTORY -- Military -- Pictorial; Armed Forces; Civil-military relations; Military art and science; Israel; Electronic books; Cross-cultural studies